Constricted Canals: A New Strategy to Overcome This Challenge - Ricardo Machado; Emmanuel João Nogueira Leal Silva; Luiz Pascoal Vansan (Case Reports in Dentistry)
Negotiation of constricted canals can be a challenge during endodontic treatment. Over the years, several strategies have been presented in order to overcome the difficulties imposed by this anatomical feature. This paper presents three cases using a different protocol from that recommended by the manufacturer of the Protaper System in order to facilitate the negotiation of constricted canals. These cases suggest that the modified protocol shown is able to perform the shaping process with less resistance, reducing the risk of instrument separation and performing an effective process to reach the apical thirds in constricted canals.